Green Computing Technologies and Computing Industry in 2021 - Sabban, Albert (IntechOpen, 2021)
The book presents innovations in green computing technologies. A large number of computing devices and cellular phones being produced and discarded is hurtling us toward a global environmental disaster. In the last fifty years, the earth has experienced rapid changes in climate, increasingly severe droughts, rising seawater levels, seawater acidification, increased depletion of groundwater reserves, and the global rise of temperature. Green computing technologies are crucial in protecting our universe from environmental hazards and pollution. Over four sections, this book examines green computing industries and technologies. Chapters cover such topics as wideband systems, Internet connectivity, the environment, and more.